2011
DOI: 10.1007/s10059-011-0072-0
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Localization of the Actin-Bundling Protein Cortexillin I during Cell Migration

Abstract: Cortexillins are actin-bundling proteins that play a critical role in regulating cell morphology and actin cytoskeleton reorganization in Dictyostelium. Here, we investigated dynamic subcellular localization of cortexillin I in chemotaxing Dictyostelium cells. Most of the cortexillin I was enriched on the lateral sides of moving cells. Upon chemoattractant stimulation, cortexillin I was rapidly released from the cortex followed by a transient translocation to the cell cortex with a peak at ~5 s and a subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The different results from the two laboratories might be due to the different assays used and/or differences in the parental cell strains. Cha and Jeon (2011) also observed that ctxA − /B − cells are flatter and rounder and chemotax more slowly than WT cells and that aggregation is inhibited and development does not proceed to completion in ctxA − /B − cells.…”
Section: Resultsmentioning
confidence: 74%
“…The different results from the two laboratories might be due to the different assays used and/or differences in the parental cell strains. Cha and Jeon (2011) also observed that ctxA − /B − cells are flatter and rounder and chemotax more slowly than WT cells and that aggregation is inhibited and development does not proceed to completion in ctxA − /B − cells.…”
Section: Resultsmentioning
confidence: 74%
“…It is known that cells form actin foci at their bottoms, which are exhibited by GFP-coronin, a marker protein for newly formed F-actin ( Fig. 2B ) ( Cha and Jeon, 2011 ; Jeon et al, 2007b ). GFPLD was found at foci at the bottom of cells, similar to the actin foci shown by GFP-coronin.…”
Section: Resultsmentioning
confidence: 99%
“…The myosin II , gCA/sGC , and gbp a/b null strains were obtained from the DictyBase Stock Center. The expression plasmids for GFP-coronin and RFP-coronin were described previously ( Cha and Jeon, 2011 ; Jeon et al, 2007b ). For expression of GFP-RapGAP3, the full coding sequence of rapGAP3 cDNA was generated by RT-PCR, cloned into the Bgl II- Xho I site of pBluescript KS (−), sequenced, and subcloned into the expression vector pEXP-4(+) containing a GFP fragment ( Jeon et al, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The actin cytoskeleton is involved in an array of vital cellular functions and has a pronounced influence on many aspects of skin biology [ 14 , 15 , 16 ]. Despite the structural role of the cytoskeleton, it is highly dynamic and can be rapidly modified to facilitate changes in cell structure during vesicle-organelle transport, cell-cell interactions, cell-extracellular matrix interactions and cell adhesion and motility [ 17 , 18 , 19 ]. The cytoskeleton comprises a network of filamentous (F)-actin, microtubules, intermediate filaments and stress fibres, all working together to mediate the continual remodelling, assembly and severing needed to generate the mechanical force required for cellular contraction, adhesion and motility [ 20 ].…”
Section: The Actin Cytoskeletonmentioning
confidence: 99%